Advancing ex vivo functional whole-organ prostate gland model for regeneration and drug screening - Karthikeyan Subbiahanadar Chelladurai; Jackson Durairaj Selvan Christyraj; Kamarajan Rajagopalan; Johnson Retnaraj Samuel Selvan Christyraj (Scientific Reports)
Abstract Model organisms are vital for biomedical research and drug testing but face high costs, complexity, and ethical issues. While newer techniques like organoids and assembloids have shown improvements, they still remain inadequate in addressing all research needs. In this study, we present a new method for maintaining the prostate gland of the earthworm, Eudrilus eugeniae ex vivo and examine its potential for regeneration and drug screening. We successfully maintained the earthworm prostate gland in cell culture media for over 200 days, with observed beating behavior confirming its viability. Apoptotic staining and histological analysis show no significant changes, indicating that the prostate gland remains stable. However, significant overexpression of H3 and H2AX on the 10th and 50th days suggests stem cell proliferation and differentiation. Alkaline phosphatase expression analysis confirmed that the stem cell niche is localized to the anterior region. Remarkably, the posterior region of the prostate gland demonstrated significant regenerative capacity, with complete regeneration occurring within 45 days following amputation. Furthermore, treatment with valproic acid enhanced posterior regeneration, leading to full restoration within 12 days. This study confirms the feasibility of maintaining the prostate gland of earthworms in an ex vivo setting, providing a valuable model for studying regeneration and conducting drug screening.